Preliminary Study on the Development of Infographic-Based Islamic Education Teaching Materials to Improve Soft Skills for High School Students in Surakarta - Wulandari, Pramesti; Asrowi, Asrowi; Djono, Djono (Jurnal Pendidikan Agama Islam, 2022)
Purpose – This research aims to conduct an initial assessment of students' attitudes in high school, with a focus on Islamic education, which is one of the benchmarks in soft skills development activities. Design/methods/approach – This study uses research and development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) with three stages in it, namely the preliminary, development, and testing stages. To increase students' soft skills, an infographic-based Islamic Religious Education teaching material was designed in this study. Findings – According to preliminary research conducted at senior high schools in Surakarta with class XI subjects, Islamic learning does not provide opportunities for students to improve their soft skills. This is requiring the development of learning tools, one of which is infographic-based teaching materials, to assist in achieving the expected competencies. Research limitations – This study focuses on acquiring Islamic education in high school, with a focus on the limitations of development in teaching materials that affect students' ability to obtain competencies in the form of soft skills. Originality/value – A preliminary investigation into the development of teaching materials in Islamic education courses, namely for senior secondary school, was studied further in this study. The development of soft skills is one of the things that is actively supported in the development of character education in Indonesian schools.